Biologically Induced Changes in the Partitioning of Submicron Particulates Between Bulk Seawater and the Sea Surface Microlayer. Issue 2 (24th January 2022) - Crocker, Daniel R.; Deane, Grant B.; Cao, Ruochen; Santander, Mitchell V.; Morris, Clare K.; Mitts, Brock A.; Dinasquet, Julie; Amiri, Sarah; Malfatti, Francesca; Prather, Kimberly A.; Thiemens, Mark H.
Abstract: Studies over the last two decades have shown that submicron particulates (SMPs) can be transferred from the seawater into sea spray aerosol (SSA), potentially impacting SSA cloud seeding ability. This work reports the first concurrent bulk and sea surface microlayer (SSML) SMP (0.4–1.0 μm) measurements, made during two mesocosm phytoplankton blooms in a region devoid of active wave breaking and bubble formation, providing insight into how biological and physicochemical processes influence seawater SMP distributions. Modal analyses of the SMP size distributions revealed contributions from multiple, biologically related particulate populations that were controlled by the microbial loop. With negligible bubble scavenging occurring, SSML enrichment of SMPs remained low throughout both experiments, suggesting scavenging is vital for SMP enrichment in the SSML. Our findings are discussed in the context of SMP transfer into SSA and its potential importance for SSA cloud seeding ability. Plain Language Summary: Research has shown that particulates can be transferred from the ocean into sea spray aerosol (SSA) when bubbles burst at the ocean surface. This transfer is important because incorporation of seawater particulates into SSA can impact its ability to seed water and ice clouds. During the Sea Spray Chemistry and Particulate Evolution (SeaSCAPE) study, submicron particulates (SMPs, 0.4–1.0 μm) were measured daily in the sea surface microlayer (SSML), the topmost 1–1, 000 μm of the ocean surface, and the underlying bulk seawater over the course of two phytoplankton growth experiments. The objective of this study was to assess the influence of biological activity on SMP concentrations and distributions in the seawater. Our results indicate that biological growth led to increased SMP production, and the size distribution of SMPs produced was dependent on the phase of the bloom growth. Additionally, almost no SSML enrichment of SMPs occurred without active wave breaking and bubble formation, highlighting the significance of biological activity and bubble scavenging/bursting for particulate transfer into SSA. These findings are discussed in the context of potential SMP impacts on SSA cloud forming ability. Key Points: The concentration of 0.4–1.0 μm seawater particulates is higher during a phytoplankton bloom The biologically induced increase in seawater submicron particulates is size dependent and influenced by the phase of the bloom Particulate enrichment in the sea surface microlayer is low in the absence of wave breaking and bubble scavenging